Some Aspects of the Effect of Porosity on Moisture Transfer in Concrete - Ilkhom Abdullayevich Kadirov; Anvar Ishanovich Adilkhodzhaev; Ulugbek Khakimovich Abdullaev (International Journal on Orange Technologies, 2022)
The question of the influence of a complex additive on the process of moisture transfer in cement concrete is considered. The results of studies of the formation of the porous structure of concretes in the presence of modifying additives are presented and the mechanism of moisture transfer in high-quality concretes of a new generation is explained.